Sustainable Use of Gum Acacia as a Biopolymeric Additive in Ultra-High Performance Concrete - Suthan Kumar N.; Sahaya Ruben J.; Ibsa Neme M. (Advances in Civil Engineering)
The main objective of this research is to analyze whether biopolymer (gum acacia) can be used as an admixture for ultra-high performance concrete (UHPC) and to elucidate the strength, durability, microstructure, and transport properties of biopolymer (gum acacia) incorporated UHPC mixes in combination with the shrinkage reducing agent (SRA). The mechanical, thermal, and durability aspects of UHPC were studied at different ages and curing conditions by adding gum acacia in combination with the SRA. After 28 days under hybrid curing, the compressive strength increased by 22.19% and the flexural strength increased by 41.59% for 1% biopolymer addition. The highest strength and durability were obtained using the hybrid curing procedure using superplasticizer and gum acacia biopolymer at a water-binder ratio of 0.35. With an improved microstructure, the results revealed improved hydration and durability as revealed through the scanning electron microscopic (SEM) images. The SEM photographs of the concrete showed more polymorphic patterns and crystals overall relative to the UHPC with SRA, while exhibiting little to no microfractures. Through adjustment of the biopolymer proportion and adoption of a suitable curing method, this research presents a new strategy for addressing the negative impact produced by the usage of SRA in UHPC.